Syncretism and ordering in the evolution of Catalan pronominal clitic clusters - Cabré, Teresa (Borealis – An International Journal of Hispanic Linguistics, 2022)
This paper examines the 3rd person clitic combinations found in a digital corpus of Catalan texts dating from the 11th century to the first half of the 18th (the CICA) and attempts to clarify the origin of the current clitic system of colloquial non-Valencian Catalan. Scrutiny of the database shows that the locative HI (i.e., hi or its variants í/y/hic) replaced the canonical dative clitic of 3rd person clusters in the 14th century in both singular and plural forms, contrary to what has previously been claimed. The medieval patterns of usage that the data reveal are very close to those occurring in colloquial non-Valencian Catalan as it is spoken nowadays, as opposed to those seen in Valencian Catalan, where a locative clitic is no longer present. On the basis of this data, we argue that the incompatibility of plural morpheme combinations in Old—among other reasons—forced the generalization of the morpheme /i/ as a dative marker, thus converting it into the true ‘elsewhere’ item of the Catalan clitic system. The similarity between medieval and modern colloquial non-Valencian Catalan clitic forms allows us to analyze them in the same way. Specifically, we suggest there is only one clitic area for these clusters in which the HI works as a place nominal located structurally in the nominal layer.